La Suisse et l'Espagne de la République à Franco : (1936-1946) / édité par Mauro Cerutti, Sébastien Guex et Peter Huber - Cerutti, MarioGuex, SébastienHuber, Peter (1954-) (Histoire)
Bibliografía y fuentes: p. 525-575. Índice de nombres: p.583-600